2022
DOI: 10.3390/soc12020059
|View full text |Cite
|
Sign up to set email alerts
|

Urban Image at the Time of the COVID-19 Pandemic, Case Study Novi Sad (Serbia)

Abstract: The main aim of this paper is to examine how negative phenomena, such as a pandemic, can result in positive cultural shifts and an upgrade of the urban image. The research was conducted employing an in-depth interview approach at the end of 2021, based on a semi-structured protocol with 15 participants. The answers of the respondents are conditioned by the socio-demographic differences. They show the urban image and cultural opportunities of the city. The image of the city is changing under different cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Many studies also focused on the increased interest in cycling. Debates about creating urban infrastructures more suitable for pedestrian and cycling mobility were prompted by the growth in walking and bike usage for leisure and also as a commuting mode, and those debates have included renewed attention on bike‐sharing schemes (de Séjournet et al, 2022; Lukić et al, 2022; Niitamo, 2021; Nikiforiadis et al, 2022; Strömberg & Wallgren, 2022; Teixeira et al, 2021). Attention to other modes of micromobility (Li et al, 2021) also found informed city‐wide and neighbourhood policies concerned with long‐term planning for and design and management of urban green mobility infrastructure using pedestrianisation of public spaces, pedestrian‐friendly walking infrastructure, bike paths, and other cycling infrastructure (Fenu, 2021; Nikiforiadis et al, 2022; Ugolini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies also focused on the increased interest in cycling. Debates about creating urban infrastructures more suitable for pedestrian and cycling mobility were prompted by the growth in walking and bike usage for leisure and also as a commuting mode, and those debates have included renewed attention on bike‐sharing schemes (de Séjournet et al, 2022; Lukić et al, 2022; Niitamo, 2021; Nikiforiadis et al, 2022; Strömberg & Wallgren, 2022; Teixeira et al, 2021). Attention to other modes of micromobility (Li et al, 2021) also found informed city‐wide and neighbourhood policies concerned with long‐term planning for and design and management of urban green mobility infrastructure using pedestrianisation of public spaces, pedestrian‐friendly walking infrastructure, bike paths, and other cycling infrastructure (Fenu, 2021; Nikiforiadis et al, 2022; Ugolini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Despite pandemic‐triggered uncertainties and anxieties, spontaneous, self‐organised networks of support, mutual aid, and new forms of collective solidarity formed among vulnerable members of urban communities, such as the elderly, people with disabilities, and others who could not leave their houses (Apostolopoulou & Liodaki, 2021; Bartrés‐Faz et al, 2021; Cano‐Hila & Cano‐Hila & Argemí‐Baldich, 2020; Catela, 2021; Lukić et al, 2022; Paris & Ying, 2021; Roels et al, 2022; Scullion et al, 2022). Taking care of each other meant “practicing responsibility for other people’s safety” (Kokkola et al, 2022, p. 16) in public transport and in other public spaces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely, answers were sought from people who organized hiking trips to Stolovi Mountain or events in their foothills. Respondents gave their opinions on the set topics, thus contributing to the objectivity of the research [108]. The most useful and expedient answers were selected during the desk research, while the most constructive answers are given in the paper.…”
Section: Other Methodsmentioning
confidence: 99%